banner

If f(2)=10 and f'(x)=x^2f(x) for all x, find f”(2).

The aim of this question is to learn how to evaluate the values of a higher order derivative without explicitly declaring the function itself.

To solve such problems, we may need to solve the basic rules of finding the derivatives. These include the power rule and product rule etc.

According to the power rule of differentiation:

\[ \dfrac{ d }{ dx } \bigg ( x^{ n } \bigg ) \ = \ n \ x^{ n – 1 } \]

According to the product rule of differentiation:

\[ \dfrac{ d }{ dx } \bigg ( f ( x ) \ g ( x ) \bigg ) \ = \ f^{‘} (x) \ g ( x ) \ + \ f ( x ) \ g^{‘} ( x ) \]

Expert Answer

Given:

\[ f^{‘} ( x ) \ = \ x^2 \ f ( x ) \]

Substitute $ x \ = \ 2 $ in the above equation:

\[ f^{‘} ( 2 ) \ = \ ( 2 )^{ 2 } f ( 2 ) \]

\[ f^{‘} ( 2 ) \ = \ 4 \ f ( 2 ) \]

Substitute $ f(2) \ = \ 10 $ in the above equation:

\[ f^{‘} ( 2 ) \ = \ 4 \ ( 10 ) \]

\[ f^{‘} ( 2 ) \ = \ 40 \]

Recall the given equation again:

\[ f^{‘} ( x ) \ = \ x^2 \ f ( x ) \]

Differentiating the above equation:

\[ \dfrac{ d }{ dx } \bigg ( f^{‘} ( x ) \bigg ) \ = \ \dfrac{ d }{ dx } \bigg ( x^{ 2 } f ( x ) \bigg ) \]

\[ f^{ ” } ( x ) \ = \ \dfrac{ d }{ dx } \bigg ( x^{ 2 } \bigg ) \ f ( x ) \ + \ x^{ 2 } \ \dfrac{ d }{ dx } \bigg ( f ( x ) \bigg ) \]

\[ f^{ ” } ( x ) \ = \ \bigg ( 2 x \bigg ) \ f(x) \ + \ x^{ 2 } \ \bigg ( f^{‘} ( x ) \bigg ) \]

\[ f^{ ” } ( x ) \ = \ 2 x \ f(x) \ + \ x^{ 2 } \ f^{‘} ( x ) \]

Substitute $ x \ = \ 2 $ in the above equation:

\[ f^{ ” } ( 2 ) \ = \ 2 (2) \ f(2) \ + \ ( 2 )^{ 2 } f^{‘} ( 2 ) \]

\[ f^{ ” } ( 2 ) \ = \ 4 f ( 2 ) \ + \ 4 f^{‘} ( 2 ) \]

Substitute $ f ( 2 ) \ = \ 10 $ and $ f^{‘} ( 2 ) \ = \ 40 $ in the above equation:

\[ f^{ ” } ( 2 ) \ = \ 4 (10) \ + \ 4 (40) \]

\[ f^{ ” } ( 2 ) \ = \ 40 \ + \ 160 \]

\[ f^{ ” } ( 2 ) \ = \ 200 \]

Numerical Result

\[ f^{ ” } ( 2 ) \ = \ 200 \]

Example

Given that $ f ( 10 ) \ = \ 1 $ and $ f^{‘} ( x ) \ = \ x f ( x ) $, find the value of f^{ ” } ( 10 ) $.

Given:

\[ f^{‘} ( x ) \ = \ x \ f ( x ) \]

Substitute $ x \ = \ 10 $ in the above equation:

\[ f^{‘} ( 10 ) \ = \ ( 10 ) f ( 10 ) \]

Substitute $ f(10) \ = \ 1 $ in the above equation:

\[ f^{‘} ( 10 ) \ = \ 10 \ ( 1 ) \]

\[ f^{‘} ( 10 ) \ = \ 10 \]

Recall the given equation again:

\[ f^{‘} ( x ) \ = \ x \ f ( x ) \]

Differentiating the above equation:

\[ \dfrac{ d }{ dx } \bigg ( f^{‘} ( x ) \bigg ) \ = \ \dfrac{ d }{ dx } \bigg ( x f ( x ) \bigg ) \]

\[ f^{ ” } ( x ) \ = \ \dfrac{ d }{ dx } \bigg ( x \bigg ) \ f ( x ) \ + \ x \ \dfrac{ d }{ dx } \bigg ( f ( x ) \bigg ) \]

\[ f^{ ” } ( x ) \ = \ \bigg ( 1 \bigg ) \ f(x) \ + \ x \ \bigg ( f^{‘} ( x ) \bigg ) \]

\[ f^{ ” } ( x ) \ = \ f(x) \ + \ x \ f^{‘} ( x ) \]

Substitute $ x \ = \ 10 $ in the above equation:

\[ f^{ ” } ( 10 ) \ = \ f(10) \ + \ ( 10 ) f^{‘} ( 10 ) \]

Substitute $ f ( 10 ) \ = \ 1 $ and $ f^{‘} ( 10 ) \ = \ 10 $ in the above equation:

\[ f^{ ” } ( 10 ) \ = \ (1) \ + \ 10 (10) \]

\[ f^{ ” } ( 10 ) \ = \ 1 \ + \ 100 \]

\[ f^{ ” } ( 10 ) \ = \ 101 \]

5/5 - (5 votes)